2020
DOI: 10.3201/eid2608.201383
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 and Acute Pulmonary Embolism in Postpartum Patient

Abstract: We report a 36-year-old woman in Iran who sought care for left shoulder pain and cough 5 days after a scheduled cesarean section. Acute pulmonary embolism and coronavirus disease were diagnosed. Physicians should be aware of the potential for these concurrent conditions in postpartum women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
17
0
5

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 9 publications
2
17
0
5
Order By: Relevance
“…Our patient had severe fatal COVID-19 pneumonia with multi-organ failure, massive PE, MCA stroke, spleen, and kidney infarcts. This drastic case presentation concurs with linking other published cases linking stroke, large vessel occlusion, and PE with COVID-19 ( 5 , 6 , 10 , 11 ). Another prospective cohort study with autopsy findings of venous thromboembolism in patients with COVID-19 showed that deep venous thrombosis was present in 7 of 12 patients (58%) in whom venous thromboembolism (VTE) was not suspected before death, and PE was the direct cause of death in four patients ( 7 ).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our patient had severe fatal COVID-19 pneumonia with multi-organ failure, massive PE, MCA stroke, spleen, and kidney infarcts. This drastic case presentation concurs with linking other published cases linking stroke, large vessel occlusion, and PE with COVID-19 ( 5 , 6 , 10 , 11 ). Another prospective cohort study with autopsy findings of venous thromboembolism in patients with COVID-19 showed that deep venous thrombosis was present in 7 of 12 patients (58%) in whom venous thromboembolism (VTE) was not suspected before death, and PE was the direct cause of death in four patients ( 7 ).…”
Section: Discussionsupporting
confidence: 90%
“…There is a tsunami of emerging COVID-19 research indicating that COVID-19 is a multi-organ systemic disease that can cause diverse pathologic changes, such as large vessel stroke, venous thromboembolism, micro thrombosis, myocardial injury, neurological sequelae, pulmonary disease, renal and hepatic dysfunction ( [5] , [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] ).…”
Section: Introductionmentioning
confidence: 99%
“…Firstly, several studies reported the occurrence of thromboembolic phenomenon in inpatient settings, especially in ICU patients with severe or critical COVID-19 12,13,[24][25][26][27] . Secondly, in a PubMed search for papers concerning thromboembolic events after mild COVID-19 cases, we retrieved only ten articles [14][15][16][17][18][19][20][21][22][23] .…”
Section: Discussionmentioning
confidence: 99%
“…According to the last WHO report, patients with mild COVID-19 recover within two weeks 28 . A few studies reported cases of mild COVID-19 that complicated with venous thromboembolism events still in the active phase of the disease [14][15][16][17][18][19] . In contrast, in our cases, the pulmonary embolism occurred in the COVID-19 convalescence phase, when the symptoms related to the acute illness had already disappeared.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation